The translation of metaphors in Mahmoud Darwish's poetry / Randah Kullab - Randah, Kullab (2016)
The present research studies the translation of metaphor from Arabic into English in the poetry of Mahmoud Darwish. The source text is collected from different collections written by Darwish such as (Birds without wings, Leaves of the olive tree...etc.) gathered in one book titled as The Collection of Mahmoud Darwish by Mohammad Dakroob (1971). On the other hand, the target text is collected from Selected poems: Mahmoud Darwish translated by Ian Wedde and Fawwaz Tuqan (1973). This study aims to identify how metaphors are translated in Darwish's poetry and aims to investigate the sustainability of the SL metaphor meaning in translation. Indeed, all these objectives are to help translators in translating metaphor in the poetry of important poets. To achieve these objectives the study seeks the answer of the following questions: (i) What are the translational strategies used in translating metaphors of Darwish's poems from Arabic into English? (ii) How is the meaning of metaphors affected when they are translated into the TL? To answer these questions, the study analyzes and categorizes the data using the conceptual metaphor by Lakoff and Johnson (1980) along with Mandelblit (1995) and Newmark (1982, 1988) as frameworks. The study finds that Darwish's metaphors are translated either by a similar images, by a TL standard images, by a similes, by a metaphors plus sense (explanation/comment), by sense (explanation) or by deletion. The study also finds that the meaning of SL metaphor can be sustained when translated by a similar image, by a similar image plus sense (explanation), by a similar image plus a footnote, by sense (explanation), or by a simile.